Population and Development Report, Issue No. 7 - United Nations (United Nations, 2015)
Population dynamics can contribute to unsustainable patterns of production and consumption, and as a consequence to water scarcity that consists of the most significant environmental challenge in the Arab region. This report endeavors to analyze the nexus between population dynamics and water scarcity and to provide recommendations on how to improve policies and programmes addressing water scarcity in order to reduce vulnerability of particular population groups and enhance resilience of populations at risk. The report looks at water scarcity through a population lens in order to enable policymakers and governments to develop targeted and people-centered policies and programmes to tackle their water scarcity issues and to address its differential impact on specific population groups which might be more vulnerable to and less capable of coping with water scarcity.